NEXUS Gains' integrated water storage options pioneer sustainability - Nkosi, Phindiwe (CGIAR System Organization, 2023)
In a world where climate change and water scarcity pose increasing challenges, finding innovative solutions to conserve and manage water resources is critical. To this end, the CGIAR Initiative on NEXUS Gains hosted a collaborative event from 27 to 29 June in Bulawayo, Zimbabwe to discuss integrated storage options in the Shashe catchment, a sub-basin of the Limpopo River.